PENGARUH PENGELUARAN PEMERINTAH BIDANG PENDIDIKAN DAN KESEHATAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KOTA KENDARI TAHUN 2005-2019 - La Ode Andyka Trisetia; Ahmad Ahmad; Muhammad Armawaddin (JEP (Jurnal Ekonomi Pembangunan), 2022)
This research aims :(1) to analyze the Influence of Government Expenditure in Education on the Human Development Index (HDI); (2) To analyze the Effect of Government Expenditure in Health on the Human Development Index (HDI). The study data used secondary data from 2005 to 2019. Variable research is education expenditure, health and Human Development Index (HDI). Data collection methods use documentation methods. Data analysis uses multiple linear regression analysis with the help of the SPSS v.17.0 program.The results showed that (1) Government Expenditure in the Field of Education Is Not Significant to The Human Development Index. This means that the realization of education spending has not been able to improve the development of the quality of human resources. In contrast to government spending in the field of health has a significant effect on the Human Development Index. The results indicate that the realization of education spending can significantly increase the Human Development Index (HDI).